2022
DOI: 10.3390/metabo12080762
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Bifidobacteria Administration in Adult Male Rats on Plasma Metabolites: A Preliminary Metabolomic Study

Abstract: Probiotics are live microorganisms distributed in the gastrointestinal tract that confer health benefits to the host when administered in adequate amounts. Bifidobacteria have been widely tested as a therapeutic strategy in the prevention and treatment of a broad spectrum of gastrointestinal disorders as well as in the regulation of the “microbiota-gut-brain axis”. Metabolomic techniques can provide details in the study of molecular metabolic mechanisms involved in Bifidobacteria function through the analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 76 publications
(78 reference statements)
1
0
0
Order By: Relevance
“…The mean relative contents of fecal SCFAs and p values were presented in Supplementary Table S4 between the two groups. It has been reported that acetic acid, propionic acid, and butyric acid have the dominant content among SCFAs, accounting for more than 85%, 31 , 32 which is consistent with our findings that these three substances constituted most of the SCFAs contents. Then, we focused on the three SCFAs.…”
Section: Resultssupporting
confidence: 93%
“…The mean relative contents of fecal SCFAs and p values were presented in Supplementary Table S4 between the two groups. It has been reported that acetic acid, propionic acid, and butyric acid have the dominant content among SCFAs, accounting for more than 85%, 31 , 32 which is consistent with our findings that these three substances constituted most of the SCFAs contents. Then, we focused on the three SCFAs.…”
Section: Resultssupporting
confidence: 93%